identifying the reasons of electronic smoking spreading (VAPING) in the society with practical application using Analytical Factors - karaghowly, Ameer kamil (Journal of Economics and Administrative Sciences, 2021)
We have investigated in this research, the contents of the electronic cigarette (Viber) and the emergence of the phenomenon of electronic smoking (vibing) were discussed, although the topic of smoking is one of the oldest topics on which many articles and research have been conducted, electronic smoking has not been studied according to statistical scientific research, we tried in this research to identify the concept of electronic smoking to sample the studied data and to deal with it in a scientific way. This research included conducting a statistical analysis using the factor analysis of a sample taken randomly from some colleges in Bab Al-medium in Baghdad with a size of (70) views where (КМО) and a (bartlett) tests have been used to test Data matching and sample sufficiency. Analytical operations were performed using the statistical application (SBSS), where (13) variables were studied. After the analysis, four basic factors were obtained. The phenomenon was explained by the values ​​of different variations. and the Cumulative variance for the factors equal (65.219) and this good output for this phenomenon and the variance for every one of them equals the first (29.176) and the second (14.551) and The third (11.174) and the fourth (10.318) and this variance for after rotation matrix